Licensed Rights of Well-known Brands: Legal Rules of Limited Partnership's (Commanditaire Venootschap) Position - Rumondang Siagian, Putri; ., Saidin; Ginting, Budiman; Leviza, Jelly (KnE Social Sciences, 2024)
Trademarks are becoming extremely significant due to globalization of commerce. A brand’s role in the realm of commerce is crucial since it serves as both a differentiation and a tool for out-competing rivals to capture the consumer market. Although it is still a common choice among business actors, limited partnerships (Commanditaire Venootschap) (CV) are not permitted to grant or receive licenses for well-known trademark rights. How is CV legally protected in this document as the owner or licensee of a well-known brand? This research uses normative research techniques in law, and data analysis used were prescriptive. The results of the research show that because CV as a business entity lacks the authority to act (bevoegheid), it will have consequences for the registration of a license agreement on the rights of the well-known mark if it assumes the position of making or receiving a license agreement, which under the Trademark Law can only be done by legal subjects, either recht persoon or naturlijk persoon. The management of CV, namely its limited partners, must act as a person (individual person) if it wants to grant or receive a license for well-known brand rights. Greater benefits will result if legal status is granted to resumes submitted by legal entities. Keywords: commanditaire venootschap, licence, well-known brand